Entrepreneurial intention : a study among students of higher learning institution - Lee, Wei Ni; Lim, Bao Ping; Lim, Li Ying; Ng, Huei Sern; Wong, Jia Lih (2012)
Students‟ entrepreneurial intention may be affected by different factors. Entrepreneurial intention is found to determine students‟ willingness to engage into entrepreneurial behavior in future. The main objective for this study is to understand how attitude toward the behavior, subjective norm and perceived behavioral control, entrepreneurship education and personality traits affect entrepreneurial intention of undergraduates. The primary data of this study was gathered by distributing 200 survey questionnaires to respondents at Universiti Tunku Abdul Rahman, Perak Campus. The Cronbach‟s Alpha Reliability test which can ensure high reliability result was conducted on every variable. Pearson Correlation Coefficient and Multiple Linear Regression Analysis were conducted in this study to observe independent variables (i.e. attitude toward the behavior, entrepreneurship education and personality traits). All the variables have significant relationship with entrepreneurial intention. Independent Sample T-test is used to test on personal details (i.e. gender differences and family background) of respondents in opposition to dependent variable (i.e. entrepreneurial intention). The discussion of the findings, implications of study, limitations and recommendations for future research are discussed in the end of the study